Flexible PVDF sensors for bruxism bite force measurement: A redefined instrumental approach - Bernardo Flores-Ramírez; Ernesto Suaste-Gómez; Víctor García-Limón; Fernando Angeles-Medina (PLoS ONE, 2025)
Bruxism, characterized by involuntary clenching or grinding teeth, is a prevalent condition primarily associated with oral health consequences such as dental wear, temporomandibular disorders (TMD), and masticatory muscle pain, while also being linked secondarily to tension-type headaches and sleep disturbances. Accurate measurement of bite force is valuable for assessing bruxism severity, understanding its biomechanical effects, and evaluating treatment outcomes. However, existing measurement methods often lack practicality for continuous or real-time monitoring. This study introduces a novel, noninvasive approach using flexible polyvinylidene fluoride (PVDF) capacitive sensors, leveraging PVDF’s piezoelectric properties to correlate bite force with the output frequency of a precision timer circuit. Experimental results demonstrated the sensor’s ability to measure bite forces in two bruxism scenarios. Static tests simulating clenching forces (0−80 kg) demonstrated sensor sensitivities of 0.0051–0.00533 × 103 Hz/kg, while dynamic tests simulating grinding motions (0−24 kg at 1 Hz) showed sensitivities of 0.0052–0.01019 × 103 Hz/kg. While the sensor demonstrated high sensitivity in static loading, its response to rapid force fluctuations was non-linear, suggesting a need for further optimization in dynamic applications. The sensors effectively tracked. real-time force variations while accounting for PVDF’s viscoelastic properties and minimizing thermal effects. The proposed sensor system offers flexibility and biocompatibility, making it ideal for real-time monitoring. This innovative system for measuring bite force in bruxism-simulated scenarios represents a step forward in objectively assessing this masticatory behavior. Future work will focus on integrating the sensor with digital health tools and exploring its use in detecting other valuable variables in the oral cavity.